Mean limb length discrepancy after total hip arthroplasty - Rasheed, Adnan; shaukat, Muhammad Kaleem; Alam, Farhad (Journal of Ayub Medical College Abbottabad, 2021)
Abstract Objective: In this study we determined the mean of preoperative limb length discrepancy (LLD), postoperative LLD and their difference. Previously very little literature is available on this topic in Pakistan, so the results of my study will be a useful addition in the existing as well as local literature. Also on the basis of these results, need of some preoperative planning and executing the plan in the operating room to eliminate LLD can be recommended. Design: Clinical Practice Article (Descriptive Case Series) Background: Limb length discrepancy (LLD) is one of the most common complications of primary total hip arthroplasty (THA) causing patients dissatisfaction. In this study we determined the mean of preoperative limb length discrepancy (LLD), postoperative LLD after THA and their difference. Previously very little literature is available on this topic in Pakistan, so the results of my study will be a useful addition in the existing as well as local literature. Also, on the basis of these results, need of some preoperative planning and executing the plan in the operating room to eliminate LLD can be recommended. Methods: It is a descriptive case series study (Clinical Practice Article) conducted on 44 patients undergoing primary Total Hip arthroplasty (THA) at orthopaedics department Madinah Teaching Hospital Faisalabad from Sep 2018 to Sept 2019. Patients having age between 18-70 years including both genders were studied with non-probability, consecutive sampling. Results: In our study mean of pre-operative LLD is -19.02 with standard deviation of 21.31 and mean of post-operative LLD is 7.25 mm with standard deviation of 9.46. This study tells that 91% of patients undergoing primary THA without using any method to eliminate LLD have postoperative LLD but 88.6% of patients (39 patients out of 44) have postoperative LLD in the range of 0 to ±10 mm which is not much significant. But 11.4% of patients (5 patients out of 44) have postoperative LLD >10 mm which causes functional impairment. Conclusion: We can say that in most of the patients postoperative LLD after primary THA is very minimal and within acceptable range in experienced hands but a few patients can have a significant LLD in order to gain better joint stability which can be compensated by shoe wears. Keywords: Limb length discrepancy (LLD); Total Hip arthroplasty (THA); preoperative LLD, Postoperative LLD; age and gender distribution of THA